Reflecting Management Priorities In Research Data - Morrison, Monica (My University, 2021)
Poster summarising findings of a 2014-15 study, Communicating Wildlife Research in Northern Botswana, carried out as part of Stellenbosch University CREST PhD in Science and Technology Studies. Presented at Africa Rising conference, Africa Rising: Mobilising Biodiversity Data for Sustainable Development, which took place in Cape Town, South Africa from 19 to 22 May 2015. Data collected and used in current wildlife research in northern Botswana appears to increasingly reflect the priorities of the country’s principal wildlife steward, the DWNP. While available open data is well used, development of local repositories needed to facilitate the broader scale analysis identified as a need by the Department of Wildlife and National Park’s new strategic plan is limited, supported mainly by short-term project funding. This needs to be remedied to ensure the applicability of research findings to effective wildlife management.
Keywords: research uptake; Botswana; science-policy interface